2008
DOI: 10.1063/1.3036526
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz wave generation via optical rectification from multiferroic BiFeO3

Abstract: We detected broadband coherent terahertz (THz) emission from multiferroic BiFeO 3 after illuminating a high-quality bulk single ferroelectric domain crystal with a ∼100 fs optical pulse. The dependence of the emitted THz waveform on the energy and polarization of the optical pulse is consistent with the optical rectification mechanism of THz emission. The THz emission provides a sensitive probe of the electric polarization state of BiFeO 3 , enabling applications in ferroelectric memories and ferroelectric dom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 20 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…As a result using femtosecond laser pulses, it was shown that coherent terahertz electromagnetic waves emission is possible. 12,13 More interestingly, it was shown that actually the emitted terahertz radiation reflects the ultrafast modulation of the spontaneous polarization of BFO which offers approaches to readout in nonvolatile random access memories and ferroelectric domain imaging systems. In addition, such pump-probe technique allows access to the photo-induced coherent acoustic phonons dynamics 18 which provides access to the determination of the elastic properties and also provides insight on the coupling of phonons and light.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…As a result using femtosecond laser pulses, it was shown that coherent terahertz electromagnetic waves emission is possible. 12,13 More interestingly, it was shown that actually the emitted terahertz radiation reflects the ultrafast modulation of the spontaneous polarization of BFO which offers approaches to readout in nonvolatile random access memories and ferroelectric domain imaging systems. In addition, such pump-probe technique allows access to the photo-induced coherent acoustic phonons dynamics 18 which provides access to the determination of the elastic properties and also provides insight on the coupling of phonons and light.…”
mentioning
confidence: 99%
“…8 Besides, because BFO has a small bandgap (in contrast to normal ferroelectrics), properties such as visible-light photovoltaic effect, 9,10 photostriction properties, 11 or THz electromagnetic wave generation by laser illumination have been recently explored. 12,13 The mechanisms behind these properties are not fully understood yet as some traps arising from defects or Schottky barriers at electrode interface can affect the experimental observations. 10,13 Nevertheless, it is believed that light excitation allows injection of photocarriers whose motion is driven by the built-in electric field linked to the large polarization of BFO.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, it is interesting to note that an intense light can also apply an electric field, by virtue of the optical rectification process 24 . This stems from the second-order nonlinearity also giving rise to the SHG signal.…”
mentioning
confidence: 99%